Implementation of the Simple Multi-Attribute Rating Technique (SMART) for Decision Making on the Selection of the Best Prospective Employee - Mihuandayani; Sanggilalung, Rida P.; Mamuaya, Supit (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
Human resource management is the important part of the company, it can affect the success of the company. In the process of selecting new employees at the company, several problems often occur such as ineffective time, the company still sorts out the prospective employee files conventionally and then compared them with other files for assessment, so it took a long time because there are many applicants who apply with different quality. In addition, there can be subjectivity to the data from the assessment results of prospective employees for certain reasons such as having emotional closeness with stakeholders. It needed a system to handle these problems such as Decision Support System (DSS). This study proposed the Simple Multi-Attribute Rating Technique (SMART) approach in evaluating prospective employees. There are five criteria used in this study, namely written tests, interviews, education, award certificates, and work experience. This decision support system can help stakeholders, especially the head of the company's branches, to determine the best candidate for employees with accurate and objective results. In this research, a comparison was also made between the SMART method and a manual system, which obtained an accuracy rate of 91.33% with the proposed method. The SMART method can be an effective and reliable option for selecting job candidates, as it can minimize errors and improve recruitment efficiency, thereby positively impacting company productivity and employee performance.